KREATIVITAS GURU DALAM PENANAMAN KEDISIPLINAN SHALAT FARDLU : (Studi di TPQ Al-Huda Jatirejo Diwek Jombang) - winarti, Ika; Zulaikah, Siti; Fatikah, Noor (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2023)
A teacher has a very important role in developing the character and attitude of the discipline of fardhu prayer towards students. Discipline is a firm rule where the contents and formulation of the rules are carefully thought out, fostered and developed in a more concrete way so that what is desired can be realized in accordance with what is expected. The purpose of this study was to describe teacher creativity, the discipline of fardlu prayers and the supporting and inhibiting factors faced by teachers in instilling discipline in students through fardlu prayers at TPQ Al-Huda Jatirejo Diwek Jombang. This research is a qualitative field research, the research form is descriptive qualitative using data collection techniques, namely observation, interviews, and documentation. Furthermore, data analysis was carried out using descriptive qualitative analysis. The results of the study show that: 1) Discipline of students in participating in congregational fard prayer activities has been carried out. This can be seen when it is already noon time, students who are assigned to call to prayer rush to take ablution and then call to prayer. 2) Teacher creativity in instilling discipline, namely: The teacher sets a good example. There is a contact book, There ispunishment, There is a schedule of adhan and iqomat. 3) Factors supporting teacher creativity in instilling the discipline of fardlu prayer, namely: cooperation between teachers, the existence of an adequate prayer room, and the participation of parents, while the teacher's obstacles in instilling the discipline of fardlu prayer are the lack of places for ablution, and the presence of sellers around TPQ.